DAMPAK PROGRAM YOUTH PARTNERSHIP PROJECT (YPP) OLEH ECPAT (END CHILD PROSTITUTION, CHILD PORNOGRAPHY AND TRAFFICKING OF CHILDREN FOR SEXUAL PURPOSES) DALAM MENANGANI KORBAN CHILD TRAFFICKING DI KAMBOJA PADA TAHUN 2009-2011 - Erlina Purnama Sari; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Youth Partnership Project (YPP) is an ECPAT-based Program that is grounded to combat commercial sexual exploitation of children. And to empower children and youth to voice their own right to be protected and become leaders in combating commercial sexual exploitation of children.This study use a constructivist perspective. The essence of this theory is international politics consists in an intellectual effort to develop a theory of the international system as a "social construction". ECPAT is a non-state actor, so the author use international organizations theory for this research. This study also includes the concept of human trafficking as the point of view of the theme of this studyThe result of this research is YPP impact on social change child victims of child trafficking and the increasing public awareness of the dangers of child trafficking by working with governments and NGOs in CambodiaKeywords: YPP, Cambodia, CSEC (Commercial Sexual Exploitations of Children), Child Trafficking.